Child car seats – a habitat for house dust mites and reservoir for harmful allergens - David Clarke; Michael Gormally; Jerome Sheahan; Miriam Byrne (Annals of Agricultural and Environmental Medicine, 2015)
[b]Introduction and objective[/b]. House dust mites produce allergens which can cause or aggravate diseases such as asthma, eczema and rhinitis. The objectives of this study are to quantify typical house dust mite and Der p 1 allergen levels in child car seats, and to determine external variables that may influence mite populations in cars. [b]Materials and Methods[/b]. Dust samples were collected from the child car seats and driver seats of 106 cars using a portable vacuum sampling pump over a two minute sampling period. Mites were counted and identified and results were expressed as mites per gram (mites/g) of dust, while Der p 1 content of samples were measured by enzyme-linked immunosorbent assay (ELISA). Questionnaires were completed by participants to identify environmental and behavioural effects on mite populations. Results were analysed using General Linear Model (GLM) procedures. [b]Results[/b]. Twelve species of mites, of which nine are known to produce harmful allergens, were recorded from 212 dust samples. Over 80% of drivers’ seats and over 77% of child car seats harboured dust mites with a significant correlation (p = 0.001) between the mites/g of dust and Der p 1 content recovered from each seat. A mean of 53 mites/g of dust per seat was recovered, with a mean Der p 1 level of 1.1µg/g. Over 12% of driver seats and 15% of child car seats contained house dust mite levels sufficient to be risk factors for sensitisation and allergic reactions. [b]Conclusions[/b]. Child car seats and driver seats are habitats to a range of mite species which can be present in sufficient concentrations to cause or aggravate allergen related illnesses in individuals who are genetically predisposed.